PENGARUH BULI-BULI HANGAT TERHADAP NYERI PUNGGUNG PADA IBU HAMIL TRIMESTER III DI KABUPATEN TAPANULI TENGAH TAHUN 2025 - Saragi R, Maria Magdalena; Yusniar (Jurnal Ilmiah PANNMED (Pharmacist, Analyst, Nurse, Nutrition, Midwivery, Environment, Dentist), 2025)
Background: Pregnant women in their third trimester generally experience back pain. The intensity of pain will increase with increasing gestational age due to shifts in the center of gravity and changes in body posture. Back pain during pregnancy occurs in the lumbosacral area. Because of the increasing weight of the fetus, the posture of the pregnant woman also changes, and this causes back pain. The aim of research: This study aims to determine the effect of using a warm flask on back pain in pregnant women in the third trimester. Method: This study used a quantitative design with a descriptive correlational approach. The sample of the study was pregnant women in the third trimester in Central Tapanuli Regency. The population in this study were all pregnant women in the third trimester in Central Tapanuli Regency in 2025. The purpose of the study was to determine the scale of pain before and after being given a warm bladder compress to pregnant women in the third trimester and to determine the effect of warm bladder compresses on back pain in pregnant women in the third trimester. The sampling technique used was purposive sampling. Univariate and bivariate data analysis (paired t test) The data analysis carried out to see the effect used the Wilcoxon formulation. Expected Results: The effect of using a warm bladder on back pain in pregnant women in the third trimester was obtained. This study is also expected to be the basis for the development of preventive education on pain in pregnant women in the third trimester. Conclusion: The results of this study are expected to contribute to the health sector, especially in pregnant women in the third trimester and the prevention of severe pain and pain that is at risk of being experienced for a longer time.